Enhanced Flip-FBMC visible light communication model - Abdullah Ali Qasim; Husam Noman Mohammedali; M. F. L. Abdullah; R. Talib; Haidar Zaeer Dhaam (Institute of Advanced Engineering and Science, 2021)
VLC technology is one of the most promising technologies in the generations of communications, especially 5G after the significant development of optical semiconductors, specific laser diode, and the use of FBMC modulation in the system. DCO-FBMC modulation surpasses all the disadvantages of DCO-OFDM modulation techniques, as it is characterized by high speed and large bandwidth, but this technique consumes high energy when converting a real bipolar signal into a positive unipolar by adding DC-bias. Besides the challenge of illumination distribution indoor typical room, where the drop of the illumination appears in the middle of the room, besides the power consumption. The Flip-FBMC technique was proposed to solve this challenge, which helps convert the bipolar signal into unipolar by separating the positive part from the negative part and converting it into positive and merging it using Multiplexer and then sending the signal. Besides this, the authors presented in this paper a new lighting model with 5 luminescent units, using LD instead of LED. The Flip-FBMC profile gave better energy savings and BER performance than DCO-FBMC, besides a lighting model that covers dark areas and gives high SNR for the blind area and give save power 13.14% from consumed power.